2023
DOI: 10.1186/s40900-023-00436-3
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges in involving people with lived experience of inclusion health as co-researchers in palliative and end of life research: a rapid review and thematic synthesis

Abstract: Background Co-research is a collaborative approach to research, promoting involvement of individuals with lived experience of a research area as experts by experience. Recently, the importance of co-research within palliative and end of life care (PEoLC) has been highlighted, yet few recommendations exist regarding best practice for involving inclusion health groups (i.e., groups that are socially excluded, typically experiencing multiple disadvantages that contribute to poor health outcomes). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Thematic synthesis: first choice method for rQES. 45 For example, in their rapid QES Crooks and colleagues 44 used a thematic synthesis to understand the experiences of both academic and lived experience coresearchers within palliative and end of life research. 45 Framework synthesis: alternative where a suitable framework can be speedily identified.…”
Section: Box 1 Choosing a Methods For Rapid Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thematic synthesis: first choice method for rQES. 45 For example, in their rapid QES Crooks and colleagues 44 used a thematic synthesis to understand the experiences of both academic and lived experience coresearchers within palliative and end of life research. 45 Framework synthesis: alternative where a suitable framework can be speedily identified.…”
Section: Box 1 Choosing a Methods For Rapid Qualitative Synthesismentioning
confidence: 99%
“…The CQIMG endorses three types of synthesis; thematic synthesis, framework synthesis and meta-ethnography (box 1). 43 44 Rapid QES favour descriptive thematic synthesis45 or framework synthesis,46 47 except when theory generation (meta-ethnography48 49 or analytical thematic synthesis) is a priority (table 2, item R17).…”
Section: Introductionmentioning
confidence: 99%
“…Lived Experience (LE), or “knowing from experience”, refers to people’s direct or indirect experiential knowledge of an issue or service [ 1 ]. LE involvement in mental health services and research is longstanding [ 2 , 3 ] and recognised as important in public health [ 4 7 ], where it echoes established approaches to public involvement and asset-based community development [ 8 ]. The emphasis on knowledge in LE distinguishes it from Patient and Public Involvement and Engagement (PPIE), although PPIE can be an engagement route for involving ‘experts by Lived Experience’, or ‘people with Lived Experience’ (PLE).…”
Section: Introductionmentioning
confidence: 99%
“…However, the critical overlap of these two fields is yet to be considered. A recent rapid review by this research team identified only three papers reflecting on co-production of palliative care research for inclusion health groups [ 30 ]. Within this, only one paper discussed involvement of PWLE homelessness [ 31 ].…”
Section: Introductionmentioning
confidence: 99%